Changes of consultation-liaison psychiatry practice in Italian general hospitals: A comparative 20-year multicenter study - Zerbinati, Luigi; Palagini, Laura; Balestrieri, Matteo; Belvederi Murri, Martino; Caruso, Rosangela; D’Agostino, Armando; Ferrara, Maria; Ferrari, Silvia; Minervino, Antonino; Milia, Paolo; Nanni, Maria Giulia; Pini, Stefano; et al. (Frontiers in Psychiatry, 2022)
Introduction: Conducted under the auspices of the Italian Society of Consultation Liaison Psychiatry (SIPC), the aim of this study was to describe the characteristics of Consultation Liaison Psychiatry (CLP) activity in Italy (SIPC-2 - 2018) over the past 20 years by comparing with data from the first Italian nation-wide study (SIPC-1 - 1998 ). Methods: We collected data on CLP visits of 3943 patients from 10 Italian hospitals over a period of one year. Data were compared with those from the SIPC-1 1998 study (4183 participants). Patients were assessed with the same ad-hoc 60-item Patient Registration Form recording information from five different areas: sociodemographic, hospitalization-related, consultation-related, interventions and outcome. Results: Compared with participants from the previous study, SIPC-2-2018 participants were significantly older (d=0.54 ) and hospitalized for a longer duration (d=0.20). The current study detected an increase in the proportion of referrals from surgical wards and for individuals affected by onco-hematologic diseases. Depressive disorders still represented the most frequent psychiatric diagnosis, followed by adjustment and stress disorders and delirium/dementia. Also, CLP psychiatrists prescribed more often antidepressants (Φ=0.13), antipsychotics (Φ=0.09), mood stabilizers (Φ=0.24), and less often benzodiazepines (Φ=0.07). Conclusions: CLP workload has increased considerably in the past 20 years in Italy, with changes in patient demographic and clinical characteristics. A trend towards increase in medication-based patient management was observed. These findings suggest that the psychiatric needs of patients admitted to the general hospital are more frequently addressed by referring physicians, although Italian CLP services still deserve better organization and autonomy